APPLYING FRUGAL PRINCIPLES IN FORENSIC SCIENCES IN AFRICA - Joe H Smith; Kate Simon (International Journal of Business, Law and Political Science, 2025)
Objective: This study examines how frugal principles can be applied in forensic sciences, in Africa with a focus on implementing the Sydney Declaration on forensic sciences. Method: The findings highlight significant opportunities for applying frugal principles in forensic sciences across Africa. These principles, which emphasize cost-efficiency, resource optimization, and simplicity without compromising quality, are particularly well-suited to address the challenges faced by many forensic laboratories in the region. Novelty: This study contributes to adopting frugal principles in Africa that aligns with the Sydney Declaration on forensic sciences principles. These innovations have the potential to transform Africa's forensic sciences landscape, enhancing its capacity to deliver timely, accurate, and equitable justice. Ultimately, the integration of frugal principles into forensic sciences offers a pathway to overcoming current limitations while supporting the development of robust, sustainable, and accessible forensic infrastructures across Africa